Assessing the Relevance of Cloud Computing for Micro, Small and Medium Enterprises in the Northern Region of India - Devesh Kumar; Harsh Vardhan Samalia; Piyush Verma (Studia i Materiały)
Micro Small and Medium-sized Enterprises (MSMEs) in developing economies like India face many challenges in the form of limited capital, lack of skilled manpower, and low ICT usage. Due to these constraints, MSMEs are not able to reap various benefits which modern ICT solutions offer. In such a scenario, cloud computing can be an appropriate option for such MSMEs which are looking for improving their internal processes, enhancing communication with clients and business partners, and extending their market reach through modern ICT solutions with minimum investment and efforts. Cloud computing is an innovative technique of providing the required information and communication technology (ICT) to customers on demand and on a pay-per-usage basis through the internet. This study is an attempt towards assessing the relevance of cloud computing for MSMEs in the northern region of India. Literature review and a questionnaire based survey method were used for this purpose. Perceived benefits, perceived ease of use, cost advantage, simplicity, affordability, scalability, rapid implementation and improved business continuity were the major benefits revealed in this study whereas, security, privacy, reliability and vendor lock-in concern emerged as the main challenges in using cloud computing by the MSMEs. The study is expected to provide MSMEs an initial understanding about the significance of cloud computing for their businesses by highlighting the actual benefits and challenges linked with the adoption of cloud computing.